The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.20945/2359-3997000000530
|View full text |Cite
|
Sign up to set email alerts
|

Iodine nutritional status is not a direct factor in the prevalence of the BRAFV600E mutation in papillary thyroid cancer

Abstract: Objectives: Papillary thyroid carcinoma (PTC) accounts for approximately 85%-90% of all thyroid cancers. Of the iodine-metabolizing genes, BRAFV600E is a highly specific target for PTC and may have a reciprocal causative relationship with iodide-metabolizing genes. Materials and methods: In this study, we performed a data analysis of selected quantitative studies to determine the relationship between iodine nutritional status and the prevalence of the BRAF600E mutation in patients with PTC. Five studies were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…A Korean study found that both relatively excessive iodine intake and low iodine intake appear to be important risk factors for BRAF mutations in PTC patients [ 24 ]. A recent Meta-Analysis study found that the incidence of BRAF V600E mutations in PTC patients with high iodine intake was 77.6%, which was higher than 64.61% in patients with low iodine intake and 60.15% in patients with normal iodine intake [ 7 ]. Despite a considerable body of research on the impact of iodine on thyroid cancer tumorigenesis and progression, the association involving high iodine intake and TC risk remains contentious, and the mechanisms behind iodine excess in the development of PTC are still unclear [ 25 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A Korean study found that both relatively excessive iodine intake and low iodine intake appear to be important risk factors for BRAF mutations in PTC patients [ 24 ]. A recent Meta-Analysis study found that the incidence of BRAF V600E mutations in PTC patients with high iodine intake was 77.6%, which was higher than 64.61% in patients with low iodine intake and 60.15% in patients with normal iodine intake [ 7 ]. Despite a considerable body of research on the impact of iodine on thyroid cancer tumorigenesis and progression, the association involving high iodine intake and TC risk remains contentious, and the mechanisms behind iodine excess in the development of PTC are still unclear [ 25 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Iodine intake may induce BRAF V600E gene mutations in PTC patients through various indirect pathways [ 7 ]. However, the effect of BRAF V600E gene mutation on the circ-0004851/miR-296-3p/FGF11 pathway is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations